Children with mental disorder and the law a guide to law and practice - Harbour, Anthony (London ; Philadelphia : Jessica Kingsley Publishers, 2008)
Children and young people with complex mental health needs are increasingly being cared for within specialist mental health care settings, either in the community or in in-patient facilities. With rapid social developments, it can be difficult for carers and practitioners to keep track of the law in this area. This book provides a guide to the law relating to mental health care for children and young people, their rights and entitlement to service, and discusses important issues in clinical and social care practice such as parental responsibility, Gillick competency and capacity, emergency int.
Human rights -- The Children Act -- Secure accommodation -- The Mental Health Act : professionals, relatives, safeguards and mental disorder -- The Mental Health Act : assessment, detention, treatment, discharge and other orders -- Criminal justice -- The Mental Capacity Act 2005 -- Service provision and entitlement -- The role and function of the approved social worker/approved mental health professional -- The diagnosis and management of complex mental illness in young people -- Confidentiality -- Young people, consent, refusal and psychiatric treatment.
Description based on print version record.
Includes bibliographical references and indexes.
Mode of access: World Wide Web.
Keywords: Mentally ill children -- Legal status, laws, etc. -- Great Britain; Mental health laws -- Great Britain; Mentally Ill Persons -- legislation and jurisprudence -- Great Britain; Adolescent -- Great Britain; Child -- Great Britain; Child Welfare -- legislation & jurisprudence -- Great Britain; Disabled Children -- legislation & jurisprudence -- Great Britain; Mental Competency -- legislation & jurisprudence -- Great Britain; Mental Health Services -- legislation & jurisprudence -- Great Britain; Patient Rights -- legislation & jurisprudence -- Great Britain; Electronic books; Electronic books